Micro-Algae Removal In Domestic Wastewater Using Aspergillus Flavus Soft Pellets As A Bio-Coagulant - Rajab, Ahmad Hussein (2007)

(untitled)
Nuisance due to algae problems will become more widespread and severe as our growing urban populations and industries continue to discharge their wastes into streams. Some of the problems are odour and taste, the clogging of filters, growths in pipes, cooling towers and on reservoir walls, surface water mats or blooms and toxicity. The existing chemical and physical methods used for micro-algae removal are creating undesirable effects in the water, therefore, most of the recent researches are focusing on biological removal methods due to lesser of impact on the environment and water quality and it may be a more economical alternative to some chemical and physical methods. This study used A. flavus as bio-coagulant for micro-algae removal in domestic wastewater. Jar test is used to determine the proper A. flavus dosage and retention time. It was determined that 5% (v/v) of A. flavus as optimum concentration and 12 hours as optimum retention time. At the optimum A. flavus concentration and retention time removal efficiencies were recorded as: 72.3% of micro-algae cell number, 79.5% of TSS, 78.6% of VSS, 63.5% of COD, 60% of BOD, 73.5% of nitrate, 45.1% of phosphorus, 90.6% of color, 76.1% of turbidity and pH was decreased from (7.45 – 6.9) to (7.0 – 6.5). 1.2 mm of A. flavus soft pellets size shown a high removal in comparison with 2.5mm and 4.3mm. with 1.2mm of A. flavus soft pellets size used, 71.5% of micro-algae removal, 77.9% of TSS removal, 76.1% of VSS removal, 68.6% of COD removal and 82.6% of color removal at 12 hours of retention time are recorded. The experimental results indicated that the solid capturing ability of A. flavus increased as the free surface area of A. flavus soft pellets increased. Moreover, A. flavus soft pellets capturing ability increased as retention time increased. The zeta potential result revealed that the average zeta potential of micro-algae was – 23.7 milivolt which the average zeta potential of A. flavus was + 46.1 milivolt. The charge difference between A. flavus and micro-algae may have constituted to the A. flavus ability to capture micro-algae.